2016
DOI: 10.1186/s12883-016-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination as a harbinger of lymphoma: a case report and review of primary central nervous system lymphoma preceded by multifocal sentinel demyelination

Abstract: BackgroundPrimary central nervous system lymphoma (PCNSL) may rarely be preceded by “sentinel demyelination,” a pathologic entity characterized by histologically confirmed demyelinating inflammatory brain lesions that mimic multiple sclerosis (MS) or acute disseminated encephalomyelitis (ADEM). Interpreting the overlapping radiologic and clinical characteristics associated with each of these conditions—contrast-enhancing demyelination of white matter and relapsing and remitting steroid-responsive symptoms resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 29 publications
(46 reference statements)
5
44
0
3
Order By: Relevance
“…Consistent with previous publications (2,6,7,9,12,(16)(17)(18), we show that a histologically confirmed diffuse large B cell lymphoma can initially manifest as a demyelinating lesion with prominent inflammation and no evidence of lymphoma cells, a finding often referred to as 'sentinel lesion'. Most of the literature describes patients who, similar to our cohort, underwent corticosteroid therapy prior to biopsy acquisition, thus reinforcing the view that the sequential manifestation of demyelination and diffuse large B cell lymphoma could be related to the corticosteroid treatment (2,(7)(8)(9)14).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous publications (2,6,7,9,12,(16)(17)(18), we show that a histologically confirmed diffuse large B cell lymphoma can initially manifest as a demyelinating lesion with prominent inflammation and no evidence of lymphoma cells, a finding often referred to as 'sentinel lesion'. Most of the literature describes patients who, similar to our cohort, underwent corticosteroid therapy prior to biopsy acquisition, thus reinforcing the view that the sequential manifestation of demyelination and diffuse large B cell lymphoma could be related to the corticosteroid treatment (2,(7)(8)(9)14).…”
Section: Discussionsupporting
confidence: 92%
“…Most often a clinical and pharmacological review of the cases reveals that steroids had been administered prior to biopsy acquisition. It has been suggested that the tissue features found in these biopsies may be indistinguishable from classical autoimmune inflammatory demyelinating diseases such as MS, although no studies specifically addressing this question have been reported (4,(14)(15)(16). Moreover, the utility of molecular diagnostic approaches may be limited when no histological evidence of lymphoma cells is available, thus underscoring the importance of identifying histological hallmarks for the differential diagnosis of these two entities (4,9).…”
Section: Discussionmentioning
confidence: 99%
“…12 In multiple sclerosis, the enhancing lesion of the open ring sign represents the area of active inflammation, while the non-enhancing area represents the inflammatory process in its most chronic phase. 13,14 In fact, myelinoclasis was confirmed pathologically in the present case. Although the cause of the myelinoclasis was unclear, the findings of occluded small arterioles by massive leukemia cell invasion to the Virchow-Robin space suggest ischemia as the cause of the myelinoclasis.…”
Section: Discussionsupporting
confidence: 78%
“…The discontinuous ring enhancement observed in the present case is similar to the open ring sign, and its specificity for demyelination is 93.8% . In multiple sclerosis, the enhancing lesion of the open ring sign represents the area of active inflammation, while the non‐enhancing area represents the inflammatory process in its most chronic phase . In fact, myelinoclasis was confirmed pathologically in the present case.…”
Section: Discussionsupporting
confidence: 77%
“…Кроме того, в дальнейшем у пациентки развилась зависимость от ГКС -уменьшение дозировки препаратов или прекращение терапии крайне быстро (в течение нескольких суток) приводило к выраженному ухудшению состояния. Этот признак характерен для лимфом ЦНС, однако не наблюдается при ОРЭМ и других демиелинизирующих заболеваниях, что делает его важным для проведения дифференциальной диагностики этих заболеваний [19].…”
Section: рис 2 мультифокальная диффузная крупноклеточная в-клеточнаunclassified